Electrophoretic Karyotype of the Obligate Biotrophic Parasite Plasmodiophora brassicae Wor. - Graf, H.; Sokolowski, F.; Klewer, A.; Diederichsen E.; Luerßen, H.; Siemens J.
Classical genetic analysis is not possible with the protist Plasmodiophora brassicae due to the intracellular life of this obligate biotrophic parasite. An electrophoretic karyotype has been obtained using contour-clamped homogeneous electric field gel electrophoresis to facilitate gene mapping of P. brassicae. Using two different separation conditions 16 chromosomal bands of P. brassicae were distinguished ranging in approximate size from 2.2 Mb to 680 kb. According to this determination of chromosome number and size, the total genome size of P. brassicae was estimated to be 20.3 Mb. The chromosomal bands were further designated by their hybridization pattern with repetitive elements of P. brassicae. The repetitive element H4 (1800 bp)hybridized with 14 chromosomal bands, but the sequence of H4 showed no homology to known centromere or telomere structures and revealed no repetitive motifs.
Keywords: CLUBROOT; CHROMOSOME NUMBER